A Divisibility Problem in the McKay Conjecture - Navarro, Ignacio P (2017)
The mathematical software GAP (Groups, Algorithms, Programming) offers a powerful set of tools to investigate computationally group theory. Using this software package we investigate a variation of a well-known problem in representation theory, the McKay Conjecture, that asserts that there is a bijection between two sets of complex-valued functions defined on two finite groups. In order to do so, we use the extensive group database from GAP and Kuhn's Algorithm in order to test our conjecture.